Phylogenetic Distribution and Diversity of Bacterial Pseudo-Orthocaspases Underline Their Putative Role in Photosynthesis - Klemenčič, Marina; Asplund-Samuelsson, Johannes; Dolinar, Marko; Funk, Christiane (Frontiers in Plant Science, 2019)
Orthocaspases are prokaryotic caspase homologues – proteases, which cleave their substrates after positively charged residues using a conserved histidine – cysteine dyad situated in a catalytic p20 domain. However, in orthocaspases pseudo-variants have been identified, which instead of the catalytic H-C residues contain tyrosine and serine, respectively. The presence and distribution of these presumably proteolytic inactive p20-containing enzymes has until now escaped attention. We have performed a detailed analysis of orthocaspases in all available prokaryotic genomes, focusing on pseudo-orthocaspases. Surprisingly we identified type I meta-caspase homologues in filamentous cyanobacteria. While genes encoding pseudo-orthocaspases seem to be absent in Archae, our results show conservation of these genes in organisms performing either anoxygenic photosynthesis (orders Rhizobiales, Rhodobacterales and Rhodospirillales in Alphaproteobacteria) or oxygenic photosynthesis (all sequenced Cyanobacteria, except Gloeobacter, the evolutionary earliest diverging oxyphotobacterium). Contrary to earlier reports, we were able to detect pseudo-orthocaspases in all sequenced strains of the unicellular cyanobacteria Synechococcus and Synechocystis. In silico comparisons of the primary as well as tertiary structures of pseudo-p20 domains with their presumably proteolytic active homologues suggest that differences in their amino acid sequences have no influence on the overall structures. Mutations therefore affect most likely only the proteolytic activity. Our data provide an insight into and distribution of pseudo-orthocaspases in Prokaryotes, their taxa-specific distribution, and allow suggestions on their taxa-specific function.